2015
DOI: 10.1002/jmor.20367
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal cranial ossification of the humpback whale (Megaptera novaeangliae)

Abstract: Being descendants of small terrestrial ungulate mammals, whales underwent enormous transformations during their evolutionary history, that is, extensive changes in anatomy, physiology, and behavior were evolved during secondary adaptations to life in water. However, still only little is known about whale ontogenetic development, which help to identify the timing and sequence of critical evolutionary events, such as modification of the cetacean ear. This is particularly true for baleen whales (Mysticeti), the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 52 publications
6
29
0
Order By: Relevance
“…Cranial Cavity Three fontanelles were observed in our odontocetes fetus studied: occipital, frontal, and mastoid [1] (the last one less clear) and are confused in Stenella attenuata [55]. Studies in mysticetes could not add more information for comparison with dolphins [63].…”
Section: Larynxmentioning
confidence: 84%
“…Cranial Cavity Three fontanelles were observed in our odontocetes fetus studied: occipital, frontal, and mastoid [1] (the last one less clear) and are confused in Stenella attenuata [55]. Studies in mysticetes could not add more information for comparison with dolphins [63].…”
Section: Larynxmentioning
confidence: 84%
“…X-ray microtomography and radiography was conducted with a laboratory X-ray CT system [43]. To be fully compatible with X-ray imaging and at the same time to completely represent working LIBs, we have designed and manufactured two dedicated proof-of-concept electrochemical cells: a cell for tomography (tomo-cell) and a cell for radiography (radio-cell).…”
Section: Resultsmentioning
confidence: 99%
“…This method of staging is preferred because it is the most detailed classification available for cetacean embryos and early fetuses, and also makes it possible to compare the developmental sequence of the humpback whale with that published for another cetacean (pantropical spotted dolphin; Moran et al, ). Using a staging system based on external features rather than determining the stage of the gestation using measurements such as total length of the specimens avoids errors introduced through specimen preservation (e.g., shrinkage due to alcohol preservation; Hampe et al, ). Therefore, while total length, especially of larger fetuses, can be used to help establish the growth rate of the species, it should not be used alone to estimate gestational stage.…”
Section: Methodsmentioning
confidence: 99%
“…Although little information is available on the ontogeny of baleen whales, descriptive anatomy of mysticete fetuses revealed that mineralized tooth germs develop in both upper and lower jaws in utero , but teeth never erupt, and neonates bear baleen plates (e.g., Ridewood, ; Van Van Dissel‐Scherft and Vervoort, ; Karlsen, ; Tomilin, ; Fudge et al, ). More recent work using computed tomography (CT) and other quantitative methods increased our understanding of the ossification sequence of mysticetes and other general skull growth patterns (Armfield et al, ; Roston et al, ; Hampe et al, ), but have yet to provide much information on the development of teeth or baleen. New data on gene expression during teeth and baleen development have also been collected using histology and protein‐staining techniques (Ishikawa and Amasaki, ; Ishikawa et al, ; Thewissen et al, ).…”
mentioning
confidence: 99%